Identification and Prioritization of Dimensions for Empowering Hospitalized Patients in Public Hospitals of Shahid Sadoughi University of Medical Sciences, Yazd - Dehghani Shoraki, Safar Ali; Hessam , Somayeh; Biabani Khankahdani, Roya (Health Nexus, 2024)
Identifying factors that impact patient experience is crucial for implementing strategies that support patient engagement and ultimately achieve better health outcomes. This study aimed to present a model for empowering hospitalized patients. This study is a quantitative-qualitative cross-sectional study conducted using stratified sampling with appropriate allocation in public hospitals affiliated with Shahid Sadoughi University of Medical Sciences, Yazd. The study involved 230 participants, including hospital directors, managers, matrons, supervisors, clinical and paraclinical unit heads, staff units, nurses, and physicians. Data were collected using demographic information tools and a researcher-made questionnaire designed to create a model for empowering hospitalized patients. The model's capability was determined by fitting the data using confirmatory factor analysis. Data were analyzed using SPSS version 16 and Amos version 24 software. The questionnaire designed for the patient empowerment model in hospitals comprised 8 domains and 61 items or components. In this study, the chi-square ratio to degrees of freedom was significant (p < 0.0001), indicating a good fit for the model. The Goodness of Fit Index (GFI) was estimated at 0.93, showing that the model fit was appropriate. The values of GFI and the Adjusted Goodness of Fit Index (AGFI) for the hospitalized patient empowerment model were above 0.8. Organizations and educational healthcare centers can use this model to empower patients. The necessary groundwork for enhancing patient empowerment should be provided by medical universities and affiliated hospitals.